Nutrient addition drives declines in grassland species richness primarily via enhanced species loss. (30th November 2022) - Muehleisen, Andrew J.; Watkins, Carmen R. E.; Altmire, Gabriella R.; Shaw, E. Ashley; Case, Madelon F.; Aoyama, Lina; Brambila, Alejandro; Reed, Paul B.; LaForgia, Marina; Borer, Elizabeth T.; Seabloom, Eric W.; Bakker, Jonathan D.; et al.
Abstract: Declines in grassland diversity in response to nutrient addition are a general consequence of global change. This decline in species richness may be driven by multiple underlying processes operating at different time‐scales. Nutrient addition can reduce diversity by enhancing the rate of local extinction via competitive exclusion, or by reducing the rate of colonization by constraining the pool of species able to colonize under new conditions. Partitioning net change into extinction and colonization rates will better delineate the long‐term effect of global change in grasslands. We synthesized changes in richness in response to experimental fertilization with nitrogen, phosphorus and potassium with micronutrients across 30 grasslands. We quantified changes in local richness, colonization, and extinction over 8–10 years of nutrient addition, and compared these rates against control conditions to isolate the effect of nutrient addition from background dynamics. Total richness at steady state in the control plots was the sum of equal, relatively high rates of local colonization and extinction. On aggregate, 30%–35% of initial species were lost and the same proportion of new species were gained at least once over a decade. Absolute turnover increased with site‐level richness but was proportionately greater at lower‐richness sites relative to starting richness. Loss of total richness with nutrient addition, especially N in combination with P or K, was driven by enhanced rates of extinction with a smaller contribution from reduced colonization. Enhanced extinction and reduced colonization were disproportionately among native species, perennials, and forbs. Reduced colonization plateaued after the first few (<5) years after nutrient addition, while enhanced extinction continued throughout the first decade. Synthesis . Our results indicate a high rate of colonizations and extinctions underlying the richness of ambient communities and that nutrient enhancement drives overall declines in diversity primarily by exclusion of previously established species. Moreover, enhanced extinction continues over long time‐scales, suggesting continuous, long‐term community responses and a need for long‐term study to fully realize the extinction impact of increased nutrients on grassland composition. Abstract : High rates of colonizations and extinctions underly the richness of grassland communities. Nutrient enhancement drives declines in richness by disrupting this approximate equilibrium primarily by continuous, long‐term exclusion of previously established, more resource‐conservative and native species. Fewer new colonizations also contribute to declines in richness with nutrient addition, but to a much smaller degree and at shorter time‐scales.